Study on different underwater energy harvester arrays based on flow-induced vibration. (15th March 2022) - Sui, Guangdong; Shan, Xiaobiao; Tian, Haigang; Wang, Lele; Xie, Tao
Highlights: When the flow rate is high, the change of the L and H has a great influence on the of the PEH array. The single-row parallel-arranged array (PEH-2P and PEH-3P) can improve the system's initial vibration velocity and half-frequency bandwidth. The single-row series-arranged array (PEH-2S and PEH-3S) can increase the maximum energy harvesting power. The energy harvesting capacity of nine-vibrators square array is 102.4% higher than the reference value, and the initial vibration velocity is 25.95% lower than the reference value. Abstract: This paper mainly uses simulation and experimental methods to analyze the output characteristics of different piezoelectric energy harvester (PEH) arrays based on flow-induced vibration, which is mainly used in low-velocity water in a natural environment. Each PEH consists of a piezoelectric beam and an interference cylinder. The PEH arrays presented in this paper include the double-vibrators parallel array (PEH-2P), double-vibrators serial array (PEH-2S), three-vibrators parallel array (PEH-3P), three-vibrators serial array (PEH-3S), and nine-vibrators square array (PEH-9). Prototypes of the different PEH arrays are fabricated and experiments are conducted to explore the energy harvesting capacity, the maximum energy harvesting power, initial vibration velocity and half-power bandwidth of the different PEH arrays. The experimental results demonstrated that the PEH-2P and the PEH-3P can improve the system's initial vibration velocity and half-power bandwidth, but the maximum energy harvesting power of the PEH array is relatively not good. The PEH-2S and the PEH-3S can increase the maximum energy harvesting power of the PEH array, but the initial vibration velocity and half-power bandwidth of the PEH array are relatively not good. The average value of energy harvesting capacity of the PEH-9 is the largest, which is 102.4% higher than the reference value, and the initial vibration velocity of the PEH-9 is the lowest, which is 25.95% lower than the reference value. This work provides a comprehensive experimental guideline for further designing an efficient PEH array used in the low-speed water environment.